Relationship between the diet and psychiatric diseases such as depression, anxiety and attention-deficit hyperactivity disorder (ADHD) - Magdalena Kozyra; Patryk Zimnicki; Justyna Kaczerska; Natalia Śmiech; Martyna Nowińska; Joanna Milanowska (Kazimierz Wielki University, 2020)
Introduction: Some people try to treat psychiatric diseases such as attention-deficit hyperactivity disorder (ADHD), depression and anxiety by practising some diets. But do they even work and have any scientific confirmation? The aim of the study: The aim of this study is to find out the relationship and influence of the diet on psychiatric diseases such as ADHD, depression and anxiety. Material and method: The research of the scientific articles was made on a database of PubMed and Google Scholar. Description of the state of knowledge: The results indicate that the lack of some nutrients such as vitamins B1, B2, B3, B6, B12, C, A, D, E, folic acid, zinc, iodine, selenium, iron, calcium, potassium, phosphorus, magnesium and chrome may increase the risk of having depression symptoms. Unhealthy diet full of trans fats, red meat and lacking of fruit and vegetables may also lead to depression. Similar results were find due to the anxiety level and the diet. When it comes to ADHD, children with this disease had lower level of vitamins B12, B6, D and folic acids. Among the newly diagnosed celiac disease people, the majority showed ADHD symptoms. After the introduction of the gluten-free diet, the symptoms of the disease subsided. Summary: The results show the huge influence of the diet on the diseases such as depression, anxiety and ADHD